The Development of a Phytopathogenic Fungi Control Trial: Aspergillus flavus and Aspergillus niger Infection in Jojoba Tissue Culture as a Model - Nawal Abd El-Baky; Raoufa Ahmed Abdel Rahman; Mona Mohammed Sharaf; Amro Abd Al Fattah Amara (The Scientific World Journal)
After introducing the idea of using concentrations equal to or less than the minimum inhibition concentration (MIC) of some active chemical compounds for evacuating microbial cells, different types of microbes were evacuated. The original protocol was given the name sponge-like protocol and then was reduced and modified from a microorganism to another to prepare microbial ghosts for various applications such as immunological applications, drug delivery, and isolation of DNA and protein. Fungal pathogens that infect plants critically affect cost effectiveness, quality, and quantity of their production. They kill plant cells and/or cause plant stress. Plant fungal infections can originate from many sources such as infected soil, seeds, or crop debris causing diseases and quality losses around the world with billions of US dollars annually as costs of the associated productivity loss. This study focused on the application of the sponge-like protocol in protecting in vitro tissue cultures of plants against fungal pathogens. This can be useful for research purposes or may be developed to be introduced in field applications. Aspergillus flavus and Aspergillus niger infection in tissue culture of jojoba (Simmondsia chinensis (Link) Schn.) was used as a model to establish the employment of this protocol to control plant fungal diseases. The best conditions for A. flavus and A. niger ghosts production previously mapped by randomization experimental design (reduced Plackett–Burman experimental design) were used to prepare fungal ghosts. SDS, NaOH, NaHCO3, and H2O2 were used in their MIC (+1 level) or minimum growth concentration (MGC, −1 level) according to the determined optimal experimental design. The release of both of DNA and protein from the fungal cells was evaluated spectrophotometrically at 260nm and 280nm, respectively, as an indicator for cell loss of their cytoplasm. Fungal ghost cells were also examined by transmission electron microscopy. After confirming the preparation of high-quality fungal ghost cells, the same conditions were mimicked to control plant fungal infection. Jojoba grown in tissue culture was sprayed with fungal cells (about 103 CFU) as a control experiment or fungal cells followed by treatment with solution (a) represents the fungal ghost cells formation calculated critical concentration (FGCCC) of SDS, NaOH, and NaHCO3 and then treatment with solution (b) represents H2O2 FGCCC. The plant was examined on day 0 (plant grown before any infection or infection followed by treatment), day 5 (plant at day 5 after infection or infection followed by treatment), and day 10 (plant at day 10 after infection or infection followed by treatment). We observed fungal growth in case of control experiments at days 5 and 10 on the tissue culture medium, as well as plant, and the absence of any fungal growth in case of plant treated with FGCCC even after day 10. We recommend using this FGCCC in the form of chemical spraying formulation to treat the plants aiming to control different plant fungal infections in in vitro tissue culture systems or applied in field.